2000
DOI: 10.1034/j.1600-0447.2000.102001019.x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of prisoners on remand: psychiatric prevalence, incidence and psychopathology in solitary vs.non‐solitary confinement

Abstract: Different levels of stress give rise to different incidence of psychiatric morbidity among remand prisoners. The surplus of incident disorders among SC prisoners is related to SC, which may act as a mental health hazard.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
3
8

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(71 citation statements)
references
References 0 publications
2
58
3
8
Order By: Relevance
“…Newer methodologies developed for studying intra-individual change are less impacted by attrition rates. Although conclusions from these studies are limited by methodological weaknesses, both Andersen et al (2000) and demonstrated that segregated populations have more psychological disorders at the start than comparison subjects. However, these two studies provide conflicting evidence on whether conditions get worse over time.…”
Section: Longitudinal Designsmentioning
confidence: 99%
See 2 more Smart Citations
“…Newer methodologies developed for studying intra-individual change are less impacted by attrition rates. Although conclusions from these studies are limited by methodological weaknesses, both Andersen et al (2000) and demonstrated that segregated populations have more psychological disorders at the start than comparison subjects. However, these two studies provide conflicting evidence on whether conditions get worse over time.…”
Section: Longitudinal Designsmentioning
confidence: 99%
“…Only two recent studies were found that followed inmates for longer time periods after placement in segregation (Andersen et al, 2000;Andersen, Sestoft, Lillebaek, Gabrielsen, & Hemmingsen, 2003;. Andersen et al (2000) studied participants over a 4 month period, but the majority of participants had data for less than a month.…”
Section: Longitudinal Designsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Bezug auf Prävalenzmessungen psychischer Auffälligkeiten und Störungen bei jugendlichen und heranwachsenden Inhaftierten liegt im deutschen Sprachraum ein erhebliches Forschungsdefizit vor (Köhler, Müller, Hinrichs, 2007). Bereits gut untersucht ist, dass erwachsene Inhaftierte im Vergleich zur Normalbevölkerung deutlich erhöhte Prä-valenzraten psychischer Störungen aufweisen (Andersen et al, 2000;Eckert, Brodbeck, Jürgens, Landerschier, Reinhardt, 1997;Fazal u. Danesh, 2002;Frädrich u. Pfäfflin, 2000). Internationale Studien zeigen, dass solche Unterschiede zur vergleichbaren Allgemeinbevölkerung auch bei jugendlichen Inhaftierten replizierbar sind (American Academy of Pediatrics/Comitee on Adolescence, 2001;Doreleijers, Moser, Thijs, van Engeland, Beyaert, 2000;Garland et al, 2001;Gosden, Kramp, Gabrielsen, Sestoft, 2003;Plattner et al, 2007;Teplin, Abram, McClelland, Dulcan, Mericle, 2002;Ulzen u. Hamilton, 1998).…”
unclassified
“…It seems evident that the conditions of detention play an important role (Bourgeois, 1997;Andersen et al, 2000;Vasseur, 2001). Suspected contributing factors to insomnia can be grouped into four categories.…”
Section: Characteristics and Causes Of Insomnia In Places Of Detentionmentioning
confidence: 99%